Improving the international prognostic index score using peripheral blood counts: Results of a large multicenter study involving 520 patients with diffuse large B cell lymphoma. Issue 4 (17th June 2020) - Marcheselli, Raffaella; Bari, Alessia; Tadmor, Tamar; Marcheselli, Luigi; Cox, Maria Christina; Papotti, Robel; Ferrari, Angela; Baldini, Luca; Gobbi, Paolo; Levy, Ilana; Pugliese, Giuseppe; Federico, Massimo; et al.
Abstract: The main purpose of this study was to assess whether it is possible to improve the prognostic impact of international prognostic index (IPI) score by combining it with peripheral blood counts. Thus, we evaluated the prognostic power of lymphocyte, neutrophil, and monocyte counts in 520 patients with diffuse large B cell lymphoma treated with R‐CHOP, confirming that these parameters have a strong impact on overall survival (OS). Using revised IPI (R‐IPI), 44% of patients were categorized as poor‐risk and showed an OS at 5 years of 46%. As OS at 5 years of the 520 patients is 67%, it is clearly evident that R‐IPI tends to overestimate the proportion of patients with poor prognosis. Accordingly, in an attempt to improve the discriminating power of R‐IPI, we evaluated and compared three different scores by combining the neutrophil lymphocyte ratio (NLR) and absolute monocyte count (AMC) with the following values: (a) IPI score 3‐5, (b) age > 60 years and performance status, (c) age  ≥ 65 years and LDH > ULN. The three indexes studied, had a similar 5 years OS for the high‐risk group (46%‐52%), but the proportion of patients classified as poor‐risk were 37%, 20%, and 32%, respectively, which are lower than 44% identified with R‐IPI. Thus, while R‐IPI overestimates the number of high‐risk patients, after applying our models, it is possible to recognize patients who are truly at high‐risk. Of the three scores, the most accurate appears to be that based on NLR, AMC, LDH > ULN and age ≥ 65 years, which identifies 32% of high‐risk patients, correlating well with what is seen in clinical practice.